TENAGA KERJA, MODAL KERJA DAN TEKNOLOGI PENGARUHNYA TERHADAP PENDAPATAN NELAYAN DESA BAMBU KECAMATAN MAMUJU - Mappigau, Ernawaty; Ferils, Muh. (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2020)
Abundant marine products are seen as a sector that can encourage and opportunities in increasing economic activities that can increase regional income, if it can be managed and developed to its full potential, then one of the keys to economic success has an advantage. There are several factors that affect the low income of fishermen in the area of ​​the Bamboo waters such as low working capital of fishermen, modernization in the field of fishing and shipping technology that still uses traditional fishing gear so that it affects the number of catches, the settlement of the fisherman's residence that does not reflect this healthy location is seen from the condition of the house building that is not feasible and the environment is dirty, besides that natural factors also influence the amount of income received by fishermen such as in the light of the moon where the fishermen find it difficult to get fish because the activity of the fish in the moonlight is not grouped apart from that the fish can see if there fishing boats on the surface of the sea that causes fish to stay away from fishing boats